THE MAIN PROBLEMS OF AGRICULTURE IN KAZAKHSTAN - Kusainov, Khalel; Sadu, Zhanna (THE INNOVATION ECONOMY, 2023)
The article presents the results of an assessment of the current situation in the agriculture of Kazakhstan, information on investments that affect the growth of the gross domestic product. The dynamics of exports and imports of agricultural products in 2015-2022 is analyzed as one of the priority areas for ensuring food security in our country. The article outlines the main problems of agriculture. Measures were identified to address the agricultural problems identified in the course of the study. The importance of state regulation of the agrarian sector of Kazakhstan in order to ensure the country's food security is revealed, as well as some measures of state regulation of the development of the agro-industrial complex are shown.